2021
DOI: 10.1016/j.jcyt.2020.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Local administration of allogeneic or autologous bone marrow-derived mesenchymal stromal cells enhances bone formation similarly in distraction osteogenesis

Abstract: Background aims: Distraction osteogenesis (DO) is a surgical technique to promote bone regeneration that requires a long time for bone healing. Bone marrow-derived mesenchymal stromal cells (MSCs) have been applied to accelerate bone formation in DO. Allogeneic MSCs are attractive, as they could be ready to use in clinics. Whether allogeneic MSCs would have an effect similar to autologous MSCs with regard to promoting bone formation in DO is still unknown. This study compares the effect of autologous MSCs vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…This animal model usually quickly exhibited OA phenotype around 4 weeks post-surgery, and we expected to evaluate the relative long-term therapeutic outcome (8 weeks after surgery), which may better mimic the clinical settings for the treatments of OA patients. And recent studies from our group have demonstrated allogeneic MSCs transplantation possessed similar therapeutic e cacy as autologous MSCs on bone formation of distraction osteogenesis rat model, indicating lower immune response associated to allogeneic MSCs therapy [35].…”
Section: Discussionmentioning
confidence: 81%
“…This animal model usually quickly exhibited OA phenotype around 4 weeks post-surgery, and we expected to evaluate the relative long-term therapeutic outcome (8 weeks after surgery), which may better mimic the clinical settings for the treatments of OA patients. And recent studies from our group have demonstrated allogeneic MSCs transplantation possessed similar therapeutic e cacy as autologous MSCs on bone formation of distraction osteogenesis rat model, indicating lower immune response associated to allogeneic MSCs therapy [35].…”
Section: Discussionmentioning
confidence: 81%
“…The microstructure of distal femoral metaphysis was analysed using high-resolution vivaCT 40 (Scanco Medical, Bruttisellen, Switzerland), as previously reported [ 32 , 33 ]. Image acquisition was performed at 70 kV and 114 ÎŒA, with a resolution of 17.5 ÎŒm per voxel, and the segmentation parameters for the bone from the background were fixed at Sigma = 0.8, Support = 2, and Threshold = 158–1000 [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Successful MSC homing can benefit bone formation, and emerging studies have revealed the therapeutic effect of MSC homing in skeleton-related diseases: BMSCs from osteoporotic patients or from aged and OVX mice revealed reduced migration and invasion ability, while administration of allogeneic or autologous bone marrow-derived MSCs improved bone formation in mice subjected to tibia transverse osteotomy. 313 , 314 Nevertheless, the homing ability of endogenous or transplanted MSCs to the bone marrow niche is generally faint. 315 To enhance homing, efforts have been made to target the specific molecular interactions mediating the process.…”
Section: Bone Matrixmentioning
confidence: 99%